Metode Pendampingan karang taruna terhadap Penyandang Disabilitas Fisik dan Lansia di Tamarunang Gowa - Mawar Melati; Mustari Mustafa (Jurnal Berita Sosial, 2022)
The method of mentoring youth groups for people with physical disabilities and the elderly. This study uses a qualitative research type using a sociological approach. Sources of data in this study based on primary data sources and secondary data. The instruments in this study were directly by using several field instruments in collecting data, namely through observation, interviews and documentation. After all the data has been collected, the writer analyzes the data by reducing the data, presenting the data and drawing conclusions. The results showed that the youth organizations in the Tamarunang sub-district provided assistance by using the youth assistance method for persons with physical disabilities and the elderly in the Tamarunang sub-district, namely: (a) the consultation method, (b) the learning method, (c) the transformation method and (d) the partnership method. . The obstacles experienced by youth organizations when providing assistance to people with physical disabilities and the elderly are (a) the lack of human resources (human resources) for youth members in each region, (b) low support from the local community, and (c) sources of funds.